Detection of oral Entamoeba Gingivalis and Trichomonas Tenax in adult quilombola population with periodontal disease = Detección de Entamoeba Gingivalis oral y Trichomonas Tenax en población de quilombola adulta con enfermedad periodontal - Araújo Rosa, Jamille Alves; Santos Fernandez, Matheus dos; Soares Vieira, Igor; Riscala Madi, Rubens; Moura de Melo, Cláudia (2020)
The objective was to analyze the periodontal condition severity and the occurrence of pathogenic microorganisms in the oral cavity of an adult population of an Afrodescent Community of northeastern Brazil. This is an observational and cross-sectional study performed through an oral clinical examination, using a standardized clinical record. For the subjects with periodontal disease, the bacterial biofilm was collected in a Petri dish containing 0.9% physiological solution to detect the presence of microorganisms Entamoeba gingivalis and Trichomonas tenax, and later observed under an optical microscope. Statistical analysis was performed by calculating the prevalence of periodontal disease and the frequency of the protozoa in the bacterial biofilm. Statistical significance of the relationships researched was verified by Fisher's exact test. It was evaluated 29 subjects pertaining to the Quilombola Patioba community, aged 35 to 44 years. The results showed that among the adults of the community, there was a high prevalence of periodontal disease (75.86%), being higher in the 1st and 6th sextants of the Community Periodontal Index (CPI). E. gingivalispositivity occurred in most sextants affected by gingivitis, while in the condition of periodontitis, this microorganism was not present in the 3rd, 4th and 6th sextants. In all sextants affected by periodontal disease, T. Tenax was observed when associated with gingivitis. It is worth mentioning the begging of the elaboration of health policies, social and professional commitment that foster a greater promotion of oral health and quality of life for the quilombolas of northeastern Brazil.
El objetivo fue analizar la severidad de la condición periodontal y la aparición de microorganismos patógenos en la cavidad oral de una población adulta de una comunidad afrodescente del noreste de Brasil. Este es un estudio observacional y transversal realizado a través de un examen clínico oral, utilizando un registro clínico estandarizado. Para los sujetos con enfermedad periodontal, la biopelícula bacteriana se recogió en una placa de Petri que contenía una solución fisiológica al 0,9% para detectar la presencia de microorganismos Entamoeba gingivalis y Trichomonas tenax, y luego se observó bajo un microscopio óptico. El análisis estadístico se realizó calculando la prevalencia de la enfermedad periodontal y la frecuencia de los protozoos en la biopelícula bacteriana. La significación estadística de las relaciones investigadas se verificó mediante la prueba exacta de Fisher. Se evaluaron 29 sujetos pertenecientes a la comunidad Quilombola Patioba, de 35 a 44 años. Los resultados mostraron que entre los adultos de la comunidad, hubo una alta prevalencia de enfermedad periodontal (75.86%), siendo mayor en el sexto sexto y sexto del Índice periodontal comunitario (IPC). La positividad de E. gingivalis se produjo en la mayoría de los sextantes afectados por gingivitis, mientras que en la condición de periodontitis, este microorganismo no estaba presente en los sextantes tercero, cuarto y sexto. En todos los sextantes afectados por enfermedad periodontal, se observó T. Tenax cuando se asoció con gingivitis. Vale la pena mencionar el inicio de la elaboración de políticas de salud, compromiso social y profesional que promuevan una mayor promoción de la salud oral y la calidad de vida de las quilombolas del noreste de Brasil.
En revista Odóvtos, vol. 22, no. 2 (mayo-agosto 2020)
Descripción basada en el contenido visto el 09 de octubre, 2024
También disponible en formato HTML y EPUB